Congenital Tuberculosis in a Neonate: A Diagnostic Dilemma - Raj, P; Sarin, YK (Journal of Neonatal Surgery, 2014)
Though tuberculosis (TB) among pregnant women is not unusual in our country, documented cases of congenital tuberculosis are rare. Diagnosis is often difficult as signs and symptoms in a neonate are non- specific. Maternal history of tuberculosis is often missed, as many of them are asymptomatic. Here we present a neonate who was operated in view of intestinal obstruction which intra operatively showed disseminated abdominal tuberculosis with infected ascites.